Kejahatan Perdagangan Manusia Sebagai Predicate Crime Dalam Undang – Undang Tindak Pidana Pencucian Uang - Grace Novelia Boru Tampubolon, Ombun; Trihastuti, Nanik (UNES Law Review, 2024)
Human trafficking is a serious crime that involves the exploitation of individuals through forced labor, slavery, or sexual exploitation. In Indonesia, this crime is recognized as a predicate crime in the Anti-Money Laundering Law. This recognition demonstrates the government's commitment to tackling human trafficking and preventing attempts to disguise the proceeds of such crimes through money laundering. The crime of human trafficking not only affects the economy and security, but also constitutes a serious violation of human rights. Law enforcement against this crime requires strong coordination between various institutions, increased capacity of law enforcement, and international cooperation. In addition, special attention needs to be paid to the protection and rehabilitation of victims to ensure their recovery and reintegration into society. Public education and enforcement of financial regulations are also important to prevent and detect money laundering activities related to human trafficking. This comprehensive approach is expected to create a safer and fairer environment and reduce the rate of human trafficking and money laundering in Indonesia.